Apocalyptic Imaginings Journal for Religion, Film and Media - John Lynch (Journal for Religion, Film and Media, 2019)
The thematic section of this issue of JRFM deals with apocalyptic imaginings in literature and film. The articles address issues such as authority, authenticity, belief, imagining social futures, and art as social laboratory. Throughout, the authors employ the lens of "the apocalyptic" to demonstrate how media can address broader socio-political and psychological issues. They can serve as a kind of social barometer to help us identify contemporary angst, anxieties, hopes, and dreams. Doing so, the authors highlight that "the apocalyptic" serves as useful analytical tool that allows us to learn something about society that might otherwise remain hidden. As such, they go back to the Greek origins of the word and show that "apocalyptic work" is the work of revealing and unveiling - both for artists and creators of media texts and for academics as scholars of contemporary culture.